Simulation of flux distribution and loss calculation at three-phase transformer core with the mix 60o-45o T-joint - Dina Maizana, Maiz Ahmad; Ismail, Daut, Prof. Dr.; Rosnazri, Ali; Syafruddin, Hassan; Risnidar Chan Bahaudin, Ir. (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.